Development of a sodium chloride (NaCl) eutectic phase change material for fish cold storage applications - Risano, Ahmad Yudi Eka; Eriyadi, Riko; Irsyad, Muhammad; Sukmana, Irza; Sugiri, Agus; Saputra, Rizal Adi; Wahyudi, Heru (Jurnal Polimesin, 2025)
Sustainable marine resource management is essential, as the sea provides a vital source of nutrition for humans. Fish and shellfish are highly perishable, making effective low-temperature storage systems crucial for preserving their quality. This research developed a cold storage system utilizing Phase Change Material (PCM) for low-temperature applications. While water is commonly used as a PCM due to its excellent thermal properties, it is unsuitable for low-temperature applications because of its 0°C freezing point. To overcome this, sodium chloride (NaCl) was introduced as a solute to lower the freezing point, resulting in eutectic salt solutions with 3%, 6%, and 9% weight concentrations. Thermal characterization revealed that the 9% wt. NaCl solution exhibited the most favourable properties, achieving a freezing point of -5.8°C while maintaining a latent heat of fusion comparable to water. Experimental validation demonstrated that 5.6 kg of the 9% NaCl solution effectively maintained 5 kg of fish at approximately 0°C for 24.3 hours, with minimal temperature fluctuation. Organoleptic evaluation yielded a score of 8 at a 95% confidence level, indicating excellent preservation quality. These findings highlight the potential of NaCl eutectic solutions as cost-effective, sustainable alternatives to conventional refrigeration methods for seafood storage.